Successful mathematics problem solving using heuristics / Hwa Tee Yong … [et.al.]. - Hwa, Tee Yong; Paul Lau, Ngee Kiong; Liew, Chin Ying; Lau, Sie Hoe (2006)
This report presents the findings of a research study funded by The Malaysian Ministry of Sciences, Technology and Innovation, entitled "Successful Mathematics Problem Solving Using Heuristics'. The purpose of this study was to investigate the Form Four students' use of heuristics in solving mathematics problems. It also sought to examine the impact of heuristics teaching on students' mathematics problem solving. Multi-stage sampling method was used to select 38 secondary schools and 1675 Form Four students as the required sample. The teachers teaching these students werealso invited to participate in this study. This study, which was predominantly quantitative, consisted of two phases. Phase I was carried out in March 2005 when the participating students were given a Pre-Test. At the same time, both the participating were teachers and students were also invited to respond to the questionnaire of this study.